2017
DOI: 10.1002/cvj.12047
|View full text |Cite
|
Sign up to set email alerts
|

The Soul of Supervision: Counselor Spirituality

Abstract: Because spirituality training for counselors and supervisors is vital to counselor development, the authors examined the relationships between purpose in life, the integration of spirituality into supervision, and the supervisory working alliance among a sample of supervisors and trainees. Supervisors reported a greater sense of purpose and spiritual discussion during supervision than trainees. Trainees' personal sense of purpose was positively related to spiritual discussions with a supervisor and to an empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…The output of Table 1 states that the SD value is 0.63. If this value is combined with a logit average value of 0.0, then item difficulty level can be categorized as follows: 31,28,12,26,19,27,20 Easy 5,11,6,32,13,29,15,16,18,9,14,2,7,10 Very Easy 17, 4, 3, 8, 1…”
Section: Item Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The output of Table 1 states that the SD value is 0.63. If this value is combined with a logit average value of 0.0, then item difficulty level can be categorized as follows: 31,28,12,26,19,27,20 Easy 5,11,6,32,13,29,15,16,18,9,14,2,7,10 Very Easy 17, 4, 3, 8, 1…”
Section: Item Analysismentioning
confidence: 99%
“…Also, the supervision achieves good results and awareness of differences in the ability to be internalized by participants so that it fosters the desire to learn more about competent counselors [5] The studies mentioned are just a few of the research results that have positively impacted the supervision work alliance. Through the work alliance, the counselor's supervision will help support the running of guidance and counseling services [6]. Counselors need to have optimal skills to understand and follow the provisions in carrying out their professional activities [7].…”
Section: Introductionmentioning
confidence: 99%
“…In an examination of counseling psychology supervisees, rapport was the strongest predictor of frequency of spiritual dialogue in supervision (Weinstein, 2006). In a more recent study of counseling students and supervisors at a religious university, students who reported a higher sense of purpose indicated more discussion of spiritual issues in supervision (Garner et al, 2017). However, supervisors still perceived discussing spiritual issues more often than did supervisees (Garner et al, 2017).…”
Section: Supervision In Counselor Training Programsmentioning
confidence: 99%
“…There were broadscale accounts of most and least helpful events in individual, triadic, and group supervision (Fickling, Borders, Mobley, & Wester, 2017) and more in‐depth exploration of challenging supervisory issues, including providing corrective feedback (Borders, Welfare, Sackett, & Cashwell, 2017), nondisclosure in triadic supervision (Lonn & Juhnke, 2017), power dynamics within the supervisory relationship (De Stefano, Hutman, & Gazzola, 2017), and feedback exchanged in group supervision (Wahesh, Kemer, Willis, & Schmidt, 2017). Quantitative exploration included attention to relationships between spirituality and supervisory working alliance (Garner, Webb, Chaffin, & Byars, 2017) and complex interplays between attachment systems, supervisory relationships, and critical feedback (McKibben & Webber, 2017). Finally, Fickling and Tangen (2017) used dual autoethnography to explore their own development in feminist supervision.…”
Section: Supervisionmentioning
confidence: 99%